The Effect Using Play Method and Its Interaction with the Reciprocal and Cooperative Methods to Learning Some Basic Football Skills - Ebrahim, Taher Yahya; Ameer, Mustafa Ahmed Abdul (Journal of Social Work and Science Education, 2025)
This study’s goals were to determine the impact of teaching kids certain fundamental football skills through play and how it interacted with cooperative and reciprocal exercise approaches. Additionally, to determine which of the two approaches is more effective in teaching pupils fundamental football skills. The research community and sample were represented by the first-stage students in the College of Physical Education and Sports Sciences at the University of Babylon for the academic year 2022-2023, numbering (128 students), because these skills selected for education are within the vocabulary of the educational curriculum prescribed for this stage. We chose a sample of (22 students), as (11) students were selected for each group, and those who failed, practiced football, and were not regular in attendance were excluded, as well as what the nature of the research requires in order to simulate the independent variable (playing style). The two experimental groups were determined by (11) students in each group. The first experimental group used the play method with the interaction of the cooperative exercise method, while the second experimental group used the play method with the interaction of the reciprocal exercise method. We used the experimental method for equivalent groups. After processing the data statistically by using the (t) test for the corresponding groups in the skill tests, and the (t) test for independent samples between the two groups. We concluded that the group of the play style combined with cooperative training was more developed than the second experimental group in the skills of passing, put down and rolling. We recommend the necessity of adopting the play style and cooperative training in learning the skills of passing, put down and rolling.